Managing employee innovative behaviour through transformational and transactional leadership styles. Issue 6 (3rd June 2019) - Hansen, Jesper Asring; Pihl-Thingvad, Signe
ABSTRACT: This paper focuses on the associations between leadership styles and employee innovative behaviour. We studied the implementation of an ambitious innovation strategy in a large Danish municipality and examined how transformational and transactional leadership styles relate to innovative behaviour. We combined data from two sources rating leadership styles of immediate supervisors and employee innovative behaviour. The findings suggest that transformational leadership and one component of transactional leadership, namely verbal rewards, are positively associated with innovative behaviour. The interaction between the two shows that innovative behaviour is most likely when the leader combines transformational leadership with verbal rewards.